Menumbuhkan Jiwa Kewirausahaan Di Era Digital SMA Masehi 01 Semarang - Erlitawati Kaharudin; Hesti Fajarsari (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2021)
The use of technology for entrepreneurship has become a very important factor in driving innovation and business growth in the digital era. Technology has given entrepreneurs powerful tools to design, manage, and expand their ventures in unprecedented ways. This article delves into various aspects of utilizing technology in entrepreneurship. This includes using AI to find business ideas and leveraging them to make work more efficient. In addition, technology has enabled in-depth data analysis and a better understanding of the market, enabling entrepreneurs to make smarter decisions. This article will discuss various aspects of utilizing technology in entrepreneurship, from opportunities to challenges, as well as the importance of integrating technology with a business vision that is sustainable and has a positive impact on society.